LEADERSHIP AND JOB SATISFACTION – A REVIEW - Belias, Dimitrios; Koustelios, Athanasios (European Scientific Journal, ESJ, 2014)
The purpose of the present study is to provide a critical review of the relation between leadership and the levels of job satisfaction experienced by employees. An organization’s or institution’s leadership refers to its leader’s style of providing direction, implementing plans and motivating employees. Job satisfaction refers to the employees’ perceptions of their working environment, relations among colleagues, earnings and promotion opportunities. The review shows that contemporary job-related phenomena like job satisfaction are related to employees’ relations with colleagues and superiors, performance and perceptions of their organization’s specific culture. In addition, the employees’ preference of leadership style is likely to be affected by several factors, including demographic characteristics. It can be supported, therefore, that measuring and analyzing an institution’s leadership style in combination with its employees’ demographic and individual characteristics may lead to valuable conclusions, so that job satisfaction is promoted.